COVID-19, congenital heart disease, and pregnancy: dramatic conjunction—case report. Issue 10 (24th July 2021) - Avila, Walkiria Samuel; Kirschbaum, Marcelo; Devido, Marcela Santana; Demarchi, Lea Maria Macruz Ferreira
Abstract: Background : Epidemiological data from the COVID-19 pandemic report that patients with pre-existing cardiovascular disease have worse outcomes and higher mortality, and that pregnant women should be considered at high risk. Case summary : A 25-year-old pregnant woman on the waiting list for a heart transplant, with a history of complete atrioventricular canal surgery, mitral mechanical prosthetic implant (St Jude-27), and cardiac resynchronization therapy (Boston Scientific) was hospitalized at 30 weeks of gestation for treatment of heart failure. After 7 days of hospitalization, she had a positive RT–PCR test for severe acute respiratory syndrome coronavirus 2 with progressive worsening of her clinical condition and acute foetal distress. Hence emergency caesarean section was performed. After the birth, the patient required mechanical ventilation, progressing to multiple organ system failures. Conventional inotropic drugs, antibiotics, and mechanical ventilation for 30 days in the intensive care unit provided significant clinical, haemodynamic, and respiratory improvement. However, on the 37th day, she suddenly experienced respiratory failure, gastrointestinal and airway bleeding, culminating in death. Discussion : Progressive physiological changes during pregnancy cause cardiovascular complications in women with severe heart disease and higher susceptibility to viral infection and severe pneumonia. COVID-19 is known to incite an intense inflammatory and prothrombotic response with clinical expression of severe acute respiratory syndrome, heart failure, and thromboembolic events. The overlap of these COVID-19 events with those of pregnancy in this woman with underlying heart disease contributed to an unfortunate outcome and maternal death.